The types of subtitles in games: a classificatory proposal - Soares, Olavo Cordeiro (2017)
Based on the studies of Soares (2017), on the Scope Theory and on the Gameplay Experience concept, this article intends to define the main types of subtitles in games and how they are supposed to behave. As a result, we offer a current overview of game subtitling categories, which can be a starting point for the creation of specific rules for the field.